Trends regarding Legal Profession Advertising - Elena-Cristina Savu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Legal advertising is the advertisement of legal services provided by a lawyer or a law firm to attract potential clients. The promotion and advertisement of legal services has undergone significant transformation in recent years. The transition from the prohibition of such advertising to the current acceptance and utilization of online platforms has not been without challenges. The rapid pace of this shift raises critical questions regarding the extent to which this abrupt change impacts the fundamental and long-established principles governing the legal profession.